2013
DOI: 10.1109/tmi.2012.2221135
|View full text |Cite
|
Sign up to set email alerts
|

Study-Parameter Impact in Quantitative 90-Yttrium PET Imaging for Radioembolization Treatment Monitoring and Dosimetry

Abstract: A small positron-generating branch in 90-Yttrium ((90)Y) decay enables post-therapy dose assessment in liver cancer radioembolization treatment. The aim of this study was to validate clinical (90)Y positron emission tomography (PET) quantification, focusing on scanner linearity as well as acquisition and reconstruction parameter impact on scanner calibration. Data from three dedicated phantom studies (activity range: 55.2 MBq-2.1 GBq) carried out on a Philips Gemini TF 16 PET/CT scanner were analyzed after rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
0
29
1
Order By: Relevance
“…We did not perform absorbed dose quantification of the non-tumorous liver or lungs as these are regions of much lower 90 Y radioconcentration which may require further research and technical considerations on its quantitative accuracy by 90 Y PET [39]. However, Elschot et al have recently shown that 90 Y PET-based DVHs of the non-tumorous liver may be feasible [40].…”
Section: Discussionmentioning
confidence: 99%
“…We did not perform absorbed dose quantification of the non-tumorous liver or lungs as these are regions of much lower 90 Y radioconcentration which may require further research and technical considerations on its quantitative accuracy by 90 Y PET [39]. However, Elschot et al have recently shown that 90 Y PET-based DVHs of the non-tumorous liver may be feasible [40].…”
Section: Discussionmentioning
confidence: 99%
“…The fusion of 90 Y bremsstrahlung SPECT with X-ray computed tomography (CT) allows for attenuation correction and 3D anatomical localization of SPECT findings (i.e., SPECT/CT) [38]. This represents another distinct advantage over bremsstrahlung 2D planar and 3D SPECT only imaging [46]. …”
Section: Bremsstrahlung Radiationmentioning
confidence: 99%
“…Another closely related challenge is that the vast majority of nuclear medicine imaging systems in place around the world are not currently designed or specifically optimized for 90 Y imaging applications. While some manufacturers have provided assistance and expertise to adapt existing imaging systems for 90 Y imaging [46], most imaging centers may have to internally customize imaging protocols with little guidance or validation. It is critical that professional organizations, nuclear medicine physicians, and researchers continue to interface and actively engage the imaging system manufacturers to develop and optimize specific protocols for more consistent and comparable 90 Y image acquisition, image reconstruction, and, ideally, quantification.…”
Section: Challenges and Future Directions For 90 Y Imagingmentioning
confidence: 99%
“…The phantom design was inspired by a gel-based phantom used by Goedicke et al to overcome the problem of microsphere sedimentation (7). For this phantom, the medium used to suspend the microspheres was gelatin.…”
Section: Phantom Constructionmentioning
confidence: 99%
“…There has been recent interest in 90 Y PET with concomitant lowdose CT. Coincidence imaging of 90 Y is possible because of a minor decay branch to the 0 1 first excited state of 90 Zr, followed by b 2 b 1 internal pair production, at a low branching ratio of 31.86 6 0.47 · 10 26 (1,2). Despite background noise in the reconstructed images due to naturally occurring 176 Lu within the lutetium-based crystal of today's time-offlight PET scanners, recent studies have shown 90 Y PET quantification to be feasible and accurate (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%